2019
DOI: 10.1002/hed.25713
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of PD‐L1 and PD‐L2 in neck node metastases of head and neck squamous cell carcinoma

Abstract: Background This study aimed on evaluating the expression levels of the immune checkpoint proteins, PD‐L1 and PD‐L2, in tissue specimens of 175 oral squamous cell carcinomas (OSCC) and 33 corresponding lymph node metastases (LNM). Methods Tissue microarrays of primary OSCC and matched LNM were investigated via immunohistochemistry regarding PD‐L1/PD‐L2 expression. Results were compared for primary tumors and corresponding metastases and correlated with clinicopathological data. Results PD‐L1 expression in cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 38 publications
2
29
1
Order By: Relevance
“…PD-L1 was the most studied biomarker, analyzed in 53 studies [10,11,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][34][35][36][37][39][40][41][42][43][44][45][46]48,50,54,[59][60][61]64,65,67,68,[70][71][72][74][75][76][77][78]80,81,86]...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PD-L1 was the most studied biomarker, analyzed in 53 studies [10,11,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][34][35][36][37][39][40][41][42][43][44][45][46]48,50,54,[59][60][61]64,65,67,68,[70][71][72][74][75][76][77][78]80,81,86]...…”
Section: Resultsmentioning
confidence: 99%
“…PD-L1 expression is common in OSCC at both the transcriptional and protein levels [34,44,47,50,81]. PD-L1 expression was noted to be different between primary and metastatic sites [10,32]. In addition, PD-1, PD-L1, OX40, and CTLA-4 are overexpressed in CTCs [80].…”
Section: Discussionmentioning
confidence: 99%
“…PD-1 and PD-L1 expression currently remain the most significant tissue biomarkers. PD-L1 expression has been associated with postchemotherapy (docetaxel/platinum/5-fluorouracil regimen) status, 127 co-occurrence with p16 INK4 expression, 131 and poorer OS 124,126,128 (but improved RFS 125,129 and OS 125,130 ). Among these studies, associations between high PD-L1 expression and favorable OS were all demonstrated in post-surgery HNSCC patients.…”
Section: Predictive Tissue Markers For Egfrtargeted Therapymentioning
confidence: 99%
“…As one of the major factors in immune checkpoint activity, the clinical relevance of PD-L1 in tumor cells and tumor microenvironments is currently the subject of intense investigation. It has been shown in some studies that high levels of PD-L1 in cancer cells correlate with SCCHN tumor size, presence of regional metastases (Moratin et al, 2019;Muller et al, 2017), and poor prognosis (de Vicente et al, 2019;Moratin et al, 2019;Muller et al, 2017;Ngamphaiboon et al, 2019;Yang, Zeng, et al, 2018), whereas other studies of SCCHN demonstrated no clinical significance (Cho, Yoon, Lee, Hong, & Hong, 2011;Mattox et al, 2017;Yoshida et al, 2018).…”
mentioning
confidence: 99%